Noncancer Palliative Care: The Lost Pieces in an Acute Care Setting in Taiwan. (June 2013) - Hsu, Nin-Chieh; Lin, Yu-Feng; Shu, Chin-Chung; Yang, Ming-Chin; Ko, Wen-Je
Little is known about the picture of patients receiving palliative care in the acute care setting. The study was conducted in a medical center in Taiwan. Cancer palliative care (CPC) was performed for terminal do-not-resuscitate (DNR) patients with advanced cancers. Noncancer palliative care (NCPC) was performed for DNR patients who did not fulfill the criteria of CPC. Of the 1379 consecutive admissions, 258 patients were identified, with 193 (74.8%) requiring NCPC and 65 (25.2%) requiring CPC. The NCPC patients were older and had lower Charlson comorbidity index (2.6 vs 8.6, P < .001) than CPC patients and had poorer consciousness and more organ failure than CPC patients when recognized. Many noncancer patients without access to specialist palliative care services were treated in the acute care setting with delayed recognition.